1990
DOI: 10.1016/0166-6622(90)80029-4
|View full text |Cite
|
Sign up to set email alerts
|

The structure directing effect of cations in aqueous silicate solutions. A 29Si-NMR study

Abstract: The structure directing effect of cations in aqueous silicate solutions -a Si-29-NMR study Wijnen Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…Several researchers [10,37,38] found that Na + ions increased the dissolution rate of silica (which consequently increases the rate of ASR reaction). In contrast, other researchers [8,39] reported that the system containing K + ions appears to be reacting faster than the one containing Na + ions. In the current study, it is interesting to note that, as shown in Fig.…”
Section: Chemistry Of Pore Solutions In Mortarsmentioning
confidence: 70%
See 1 more Smart Citation
“…Several researchers [10,37,38] found that Na + ions increased the dissolution rate of silica (which consequently increases the rate of ASR reaction). In contrast, other researchers [8,39] reported that the system containing K + ions appears to be reacting faster than the one containing Na + ions. In the current study, it is interesting to note that, as shown in Fig.…”
Section: Chemistry Of Pore Solutions In Mortarsmentioning
confidence: 70%
“…In addition, the contents of Ca(OH) 2 and the expansions of mortar bars were also quantified to investigate the relationship between Cement and Concrete Research 71 (2015) [36][37][38][39][40][41][42][43][44][45] these parameters and the change in the chemistry of pore solution obtained from samples undergoing ASR. Specifically, the effects of following parameters on the chemistry of pore solution and the content of calcium hydroxide (Ca(OH) 2 ) are described: (a) length of curing time (up to 130 days), (b) temperature (23°C, 38°C, and 55°C), and (c) presence of reactive or non-reactive aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism for the condensation reaction is believed to involve a bimolecular collision between an ionised and an un-ionised silicic acid molecule as shown [5,57,62,66]. Silicic acid molecules oligomerise in such a way to produce a maximum number of siloxane (Si-O-Si) bonds and a minimum of uncondensed Si(OH) groups [5], and so the oligomers cyclise during the early stages of the process to give rings containing predominantly 3±6 silicon atoms linked by siloxane bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The tetrahydroxysiloxane Qo level in the methanol-water solution seemed to be rather low compared with results of silica dissolution studies published (5, 11). Possibly, the subsequent oligomerization reaction proceeded relatively fast compared with the monomer dissolution under our experimental conditions.…”
Section: )mentioning
confidence: 47%
“…Furthermore, the proportions of the oligomeric silicates in particular were affected by the type of solvent used for dissolution studies as is the case with silica substrates (5, 11).…”
Section: )mentioning
confidence: 99%